COMPARATIVE PROXIMATE COMPOSITION, ANTI-NUTRITIONAL ANALYSES AND ANT-MICROBIAL SCREENING OF SOME NIGERIAN MEDICINAL PLANTS - Khan, M. E.; Adebayo, K. O.; Osigbemhe, I. G.; Maliki, M.; Bolaji, A. M.; Paul, F.; Edeeje, J. P. (FUDMA JOURNAL OF SCIENCES, 2023)
The food insecurity in the world/Nigeria paves the way for more research to remedy human hunger /diseases caused by weather conditions / greenhouse effects. This study compares and validates the proximate composition, the anti-nutritional and anti-microbial screening of crude methanol extracts of three Nigerian medicinal plants; Lactuca taraxacifolia; [ moisture (10.68 ± 00%), Ash (19.48 ± 0.03%), Crude fibre (39.16 ± 0.10%), Crude Protein (7.97± 0.03%), Lipid (11.77± 0.02%), Carbohydrate (29.91± 0.13%), Oxalate > Phylate > Tannin; the inhibition zones for the most effective concentration of 50 mg / mL : Staphylococcus. aureus 45.66 ± 0.00, Escherichia coli 49.40 ± 0.01,  Salmonella typhi 42.30 ± 0.00, Streptococcus faecalis 41.90 ± 0.01]. Aframomum melegueta; {Moisture (4.36 ± 0.04 %), Ash (6.75 ± 0.03%), Crude fibre (19.92 ± 0.11 %), Protein (5.48 ± 0.04 %), Crude fat (3.60 ± 0.13%), Carbohydrate (59.49 ± 004%), Tannin > Phylate > Oxalate; S. aureus 20.22 ± 0.01, E. coli 30.21 ± 0.30, S. typhi 15.24 ± 0.11, S. faecalis 15.61 ± 0.13} and Ocimum gratissimum; [Moisture (12.43 ± 0.22%), Ash (17.77 ± 0.04%), Fibre (19.91± 0.15%), Protein (1.92 ± 0.26%), Fat (11.80 ± 0.02%), Carbohydrate (42.63 ± 0.06%), Tannin > Phylate > Oxalate; S. aureus 35.03 ± 0.00, E. coli 34.22 ± 0.71, S. typhi 32.02 ± 0.01, S. faecalis 30.01 ± 0.42]. Considering the proximate analyses, it’s seen that, A. melegueta carbohydrates is the greatest followed by O. gratissimum, then L. taraxacifolia. Their anti-nuttherapeutics and nutrients, especially during this era of food
Keywords: proximate composition; Anti-nutritional analyses; Lactuca taraxacifolia; Aframomum melegueta; Ocimum gratissimum; antimicrobial activity